2012
DOI: 10.4103/0973-1296.103654
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of Crataeva nurvala bark against testosterone and N-methyl-N-nitrosourea-induced oxidative damage in prostate of male albino rats

Abstract: Background:Antioxidant properties of Crataeva nurvala bark contains a variety of the bioactive phytochemical constituents in medicinal plants which include flavonoids, phenolic compounds, tannins, anthracene derivatives, and essential oils. Components from Crataeva nurvala bark have been accounted to play an important role in scavenging free radicals generated by mutagens and carcinogens. Androgens are the key factors in either the initiation or progression of prostate cancer by inducing oxidative stress. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(26 reference statements)
1
1
0
1
Order By: Relevance
“…Catalase and SOD activities were restored in 2K1C rats by the treatment of the Crataeva nurvala bark extract. A previous report also supports this finding that both catalase and SOD may be restored by Crataeva nurvala bark extract treatment [ 46 ]. Antioxidant enzymes are regulated by nuclear factor erythroid 2-related factor 2 (Nrf-2) which is a transcriptional factor activated against oxidative stress to stimulate tissue defense [ 50 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Catalase and SOD activities were restored in 2K1C rats by the treatment of the Crataeva nurvala bark extract. A previous report also supports this finding that both catalase and SOD may be restored by Crataeva nurvala bark extract treatment [ 46 ]. Antioxidant enzymes are regulated by nuclear factor erythroid 2-related factor 2 (Nrf-2) which is a transcriptional factor activated against oxidative stress to stimulate tissue defense [ 50 ].…”
Section: Discussionsupporting
confidence: 82%
“…This result can be supported by a previous study that reported that the ethanol extract of Crataeva nurvala stem bark showed protection in cisplatin-induced nephrotoxicity and kidney dysfunction [ 45 ]. In another study, it was revealed that oxidative stress induced by N-methyl-N-nitrosourea and testosterone elevated the concentration of MDA, which was controlled by the bark extract of Crataeva nurvala [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estes modelos são programados para desenvolverem, por exemplo, tumores prostáticos, os quais permitem os estudos diretamente relacionados com o câncer de próstata ou as neoplasias intra-epiteliais prostáticas, mas falham quando o objetivo é estudar meios de quimioprevenção ou os agentes promocionais dessas condições . O composto tem sido empregado em protocolos que testam a capacidade de indução do câncer em curto prazo por agentes promotores (POLLARD & LUCKERT, 1986e 1987POLLARD et al, 1989;POLLARD, 1992;MCCORMICK et al, 1998;PEIXOTO et al, 2016) ou então em protocolos que testam a capacidade quimiopreventiva de compostos anticâncer, quando estes inibiriam a ação da MNU (BOONE et al, 1992;BANUDEVI et al, 2011;KUMAR et al, 2012;SANCHES et al, 2013).…”
Section: N-metil-n-nitrosoureia (Mnu)unclassified